Currency boards and currency Crises. - Irwin, G (Department of Economics (University of Oxford), 2001)
This paper demonstrates how a currency board can become vulnerable to a crisis in which the policymaker is forced to devalue. The model is built from two blocks: first, incomplete information about the devaluation cost faced by the policymaker; and second, unemployment persistence. Incomplete information can result in multiple equilibria. In one class of equilibrium the policymaker has a credibility problem and maintaining the currency board is costly in terms of unemployment. If unemployment is persistent then pressure to devalue can build up over time until it becomes unbearable and the policymaker is forced to devalue.